Estimates of genetic parameters for growth, reproductive, and carcass traits in Nelore cattle using the single step genomic BLUP procedure - Kluska, Sabrina [UNESP]; Olivieri, Bianca Ferreira [UNESP]; Bonamy, Martin; Justin Chiaia, Hermenegildo Lucas [UNESP]; Braga Feitosa, Fabieli Loise [UNESP]; Berton, Mariana Piatto [UNESP]; Peripolli, Elisa [UNESP]; Antunes Lemos, Marcos Viniclus [UNESP]; Tonussi, Rafael Lara [UNESP]; Lobo, Raysildo Barbosa; Magnabosco, Claudio de Ulhoa; Di Croce, Fernando; et al. (Elsevier B.V., 2018)
This study was carried out to estimate the heritability and genetic correlations between adjusted weights at 210 (W210) and 450 (W450) days of age, scrotal circumference adjusted at 365 (SC365) and 450 (SC450) days of age, age at first calving (AFC), probability of precocious calving (PPC), stayability (STAY), ribeye area (REA), subcutaneous backfat thickness (BF), and rump fat (RF) traits. The covariance components and genetic parameters for all traits but PPC and STAY were estimated considering a linear animal model, for the remaining traits a threshold animal model was used. The single-step genomic BLUP (ssGBLUP) procedure was used for all traits, and the correlation estimates were obtained by two-traits analysis. The heritability estimated by single-trait analysis were 0.21 +/- 0.01, 0.43 +/- 0.01, 0.47 +/- 0.02, 0.52 +/- 0.02, 0.11 +/- 0.01, 0.12 (0.07-0.16), 0.37 (0.26-0.38), 0.33 +/- 0.02, 0.17 +/- 0.01 and 0.33 +/- 0.02 for W210, W450, SC365, SC450, AFC, PPC, STAY, REA, BF and RF, respectively. Growth traits (W210 and W450) showed high (0.95) genetic correlation with one another, moderate (0.30 to 0.66) with REA and scrotal circumferences, and low (0.07 to 0.20) with female reproductive traits (AFC, PPC, and STAY) and fat carcass indicator traits (BF and RF). Female reproductive traits displayed moderate (0.29 to 0.52) genetic correlations with male reproductive traits, and varied from low to moderate (0.02 to 0.35) with carcass traits. Additionally, carcass traits exhibited low to moderate (0.02 to 0.48) genetic correlations with all traits, except for the genetic correlation between BF and RF (0.73). Hence, higher genetic gains by direct selection would be obtained for W450, SC365, SC450, STAY, REA, and RF. Selection to increase growth traits might increase carcass yield and scrotal circumference, and it would not affect carcass fat content, precocity, and cow longevity indicator traits. The results of this study encourage the use of PPC in Nelore cattle since the selection for such trait would improve the productivity and longevity of the cows. The inclusion of carcass quality indicator traits such as BF or RF in selection indices would increase the genetic gain for carcass grade, but it will require further studies to estimate the economic value of these traits.
Keywords: Bos indicus; Beef cattle; Genetic correlations; Genomic information; Selection criteria